2020
DOI: 10.1186/s13046-020-01618-7
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diindolylmethane modulates aryl hydrocarbon receptor of esophageal squamous cell carcinoma to reverse epithelial-mesenchymal transition through repressing RhoA/ROCK1-mediated COX2/PGE2 pathway

Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is one of the most aggressive tumors in the world. Aryl hydrocarbon receptor (AHR) has been reported to promote tumor metastasis and epithelial-mesenchymal transition (EMT) is a vital process of conferring cancer cells capabilities of migration and invasion. However, the mechanism by which modulation of AHR can inhibit tumor metastasis remains unknown. Thus, we aim to investigate the underlying mechanism regarding reversing EMT process of ESCC through modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 43 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…High AHR expression also correlates with lymph node metastases and/or poor prognosis in inflammatory breast and esophageal squamous cell carcinomas (ESCC) [ 119 , 174 ]. In the ESCC context, AHR modulation with the partial AHR agonist 3,3′-diindolylmethane not only down-regulated Vimentin and Slug, but also inhibited the RhoA/ROCK1 pathway, which in turn suppressed COX2/PGE 2 signaling, prostaglandin E2 production, migration, metastasis and EMT [ 174 , 175 , 176 , 177 ]. This appears to be a generalizable metastasis pathway in that both RhoA/ROCK1 and PGE2 have been implicated in lung and endometrial carcinoma metastasis [ 178 , 179 , 180 , 181 ].…”
Section: Consequences Of Chronic Ahr Activity In Cancermentioning
confidence: 99%
“…High AHR expression also correlates with lymph node metastases and/or poor prognosis in inflammatory breast and esophageal squamous cell carcinomas (ESCC) [ 119 , 174 ]. In the ESCC context, AHR modulation with the partial AHR agonist 3,3′-diindolylmethane not only down-regulated Vimentin and Slug, but also inhibited the RhoA/ROCK1 pathway, which in turn suppressed COX2/PGE 2 signaling, prostaglandin E2 production, migration, metastasis and EMT [ 174 , 175 , 176 , 177 ]. This appears to be a generalizable metastasis pathway in that both RhoA/ROCK1 and PGE2 have been implicated in lung and endometrial carcinoma metastasis [ 178 , 179 , 180 , 181 ].…”
Section: Consequences Of Chronic Ahr Activity In Cancermentioning
confidence: 99%
“…However, the abnormal activation of the RhoA/ROCK1 pathway can promote carcinogenesis in many human cancers. Zhu et al revealed that diindolylmethane could reverse EMT process and inhibit esophagus cancer metastasis through repressing RhoA/ROCK1 mediated COX2/PGE pathway [19] . In lung cancer, KRAS promoted cell metastasis via activating RhoA expression [20] .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in thyroid carcinoma tissue and cell lines showed an increase in AhR expression which led to the upregulation of SLUG, which in turn repressed E-cadherin expression, an epithelial marker, and upregulated N-cadherin and fibronectin (mesenchymal markers). Other authors reported the involvement of AhR in neuroblastoma and inflammatory BC progression by promoting the establishment of an immunosuppressive TME and EMT [ 90 , 93 , 94 ].…”
Section: Fermentation Products and Catabolitesmentioning
confidence: 99%